The Implications of Halal Certification in Business Management of the Food and Beverage Industry - Ilham Habibi Lubis; Zuhrinal M Nawawi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This research discusses the food and beverage industry in Indonesia, which has shown significant growth and is an important contributor to the processing industry's GDP. This growth aligns with public awareness of the importance of consuming halal food and drinks, especially amid global trends that prioritize halal and thayibban lifestyles. Halal certification is crucial in meeting the demands of consumers who are increasingly concerned about halal products. This certification guarantees that the product has met halal and quality standards, reached a wider market, and earned consumer trust. However, there are still challenges in implementing halal certification as a whole, especially related to the lack of awareness and compliance of business actors. Research shows that halal certification has implications in business management, including its influence on marketing strategy, global market access, and operational efficiency. Sharia business management becomes relevant in this context, organizing business operations in accordance with Sharia principles to ensure compliance with the rules and principles established by Islam. By strengthening business management in accordance with sharia principles and leveraging halal certification, business players can increase competitiveness, expand markets, and build consumer trust, thereby supporting the growth of the halal food and beverage industry in Indonesia and globally. It was found that halal certification has a strategic impact in product marketing, providing global market access, and strengthening the position of business actors. Implementing sharia business management is also important for ensuring compliance with sharia principles in business operations. Thus, halal certification is the key to entering a wider market and maintaining a competitive advantage in the food and beverage industry.